Somatosensory processing in deaf and deafblind individuals: How does the brain adapt as a function of sensory and linguistic experience? A critical review - Villwock, Agnes; Grin, Konstantin (Frontiers in Psychology, 2022)
How do deaf and deafblind individuals process touch? This question offers a unique model to understand the prospects and constraints of neural plasticity. Our brain constantly receives and processes signals from the environment and combines them into the most reliable information content. The nervous system adapts its functional and structural organization according to the input, and perceptual processing develops as a function of individual experience. However, there are still many unresolved questions regarding the deciding factors for these changes in deaf and deafblind individuals, and so far, findings are not consistent. To date, most studies have not taken the sensory and linguistic experiences of the included participants into account. As a result, the impact of sensory deprivation vs. language experience on somatosensory processing remains inconclusive. Even less is known about the impact of deafblindness on brain development. The resulting neural adaptations could be even more substantial, but no clear patterns have yet been identified. How do deafblind individuals process sensory input? Studies on deafblindness have mostly focused on single cases or groups of late-blind individuals. Importantly, the language backgrounds of deafblind communities are highly variable and include the usage of tactile languages. So far, this kind of linguistic experience and its consequences have not been considered in studies on basic perceptual functions. Here, we will provide a critical review of the literature, aiming at identifying determinants for neuroplasticity and gaps in our current knowledge of somatosensory processing in deaf and deafblind individuals.